Currency Risk of Public Debt in Serbia: Current Status and European Lessons - Radosavljevic, Goran; Tomov, Vladimir (Industrija, 2018)
Currency risk, and its effect on public debt, is becoming more important in economic analysis, particularly in highly dollarized countries like Serbia. The aim of this paper is to analyse the currency structure of the public debt in Serbia and the associated risks, and to present the recommendations for improving public debt management based on international experiences. This paper analyses the currency structure of public debt of Serbia over the period 2004-2016, the comparative indicators of dollarization in Serbia and selected countries of the region, as well as the currency risk movements. The currency structure of the public debt of Serbia characterizes the predominance of three currencies – dinar, dollar and euro. Serbia is the most euroised country in the region, along with a marked highest share of dollar debt in total public debt. As a result, due to currency mismatch, the public debt of Serbia is exposed to high currency risk. Based on the presented successful examples of public debt management in Hungary and Poland, as countries with a low level of dollarization, the recommendations for improving public debt management system in Serbia are presented in the final section of our paper.